FEASIBILITY STUDY BASED ON ECONOMIC PERSPECTIVE OF COBALT NANOPARTICLE SYNTHESIS WITH CHEMICAL REDUCTION METHOD - Nandatamadini, Fira; Karina, Suci; Nandiyanto, Asep Bayu Dani (CAKRA KIMIA (Indonesian E-Journal of Applied Chemistry); Vol 7 No 1 (2019): Volume 7, Nomor 1, 2019, 2019)
ABSTRACT: Cobalt nanoparticle powder is synthesized by chemical reduction method. Cobalt nanoparticle powder is synthesized through reduction of aqueous solution of Co ions by NaBH4 using cetyltrimethylammonium bromide (CTAB) as cationic surfactant. Cobalt nanoparticles have many applications, especially in the field of technology. The successfulness of a project will produce opportunities that make it possible to advance technology in developing countries. For this reason, a feasibility study for the synthesis of cobalt powder nanoparticles is needed. This project has estimated ideal conditions for bad cases that will occur in production by adding several parameters which are raw materials and sales. This feasibility study was using two parameters which were economic analysis and evaluation techniques including Gross Provit Margin (GPM), Cumulative Net Present Value (CNPV), Break Even Poit (BEP), Payback Period (PBP). These parameters were to show potential profitability for the project. Although the IRR value of this project was not very promising, all other parameters had positive impacts. The project that used a reducing metal salt method which is an easy process and purchased relatively inexpensive equipments will provide benefits and attrac investors of this project.